2021
DOI: 10.1152/japplphysiol.00180.2021
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent short-arm centrifugation is a partially effective countermeasure against upright balance deterioration following 60-day head-down tilt bed rest

Abstract: This study investigated whether artificial gravity (AG), induced by short-radius centrifugation, mitigated deterioration in standing balance and anticipatory postural adjustments (APAs) of trunk muscles following 60-day head-down tilt bed rest. Twenty-four participants were allocated to one of three groups: control group (N=8); 30 minutes continuous AG daily (N=8); intermittent 6x5 minutes AG daily (N=8). Before and immediately after bed rest, standing balance was assessed in four conditions: eyes open and clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…While there was no statistically significant effect of 30 mins of daily AG on these balance and mobility measures, it is notable that the AG group’s decline in their SOT-5M equilibrium score with HDBR was 10.4 points less than that of control participants. Moreover, a recent study from the same campaign showed that some postural control measures declined less in bed rest for participants that received AG ( De Martino et al, 2021 ). Thus, a higher dose of AG (in terms of duration and/or magnitude) may prove beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…While there was no statistically significant effect of 30 mins of daily AG on these balance and mobility measures, it is notable that the AG group’s decline in their SOT-5M equilibrium score with HDBR was 10.4 points less than that of control participants. Moreover, a recent study from the same campaign showed that some postural control measures declined less in bed rest for participants that received AG ( De Martino et al, 2021 ). Thus, a higher dose of AG (in terms of duration and/or magnitude) may prove beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest that passive exposure to intermittent centrifugation during 60 days head down tilt bed rest do not provide protective effects to maintain control and coordination of superficial and deep lumbar spinal muscles during anticipatory adjustments to quick arm movements (De Martino et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…HDBR studies have examined the effects of artificial gravity applied via centrifugation as a potential countermeasure for spaceflight-associated brain and behavioral changes ( Frett et al, 2020 ). Recent data shows that artificial gravity does not prevent aerobic capacity declines during bed rest, although it does mitigate some muscular function decay ( Kramer et al, 2021 ) and partially counteract upright balance ( De Martino et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%